The Homerian carbon isotope excursion (Silurian) within graptolitic successions on the Midland Platform (Avalonia), UK: implications for regional and global comparisons and correlations. (2nd October 2017) - Fry, Charlotte R.; Ray, David C.; Wheeley, James R.; Boomer, Ian; Jarochowska, Emilia; Loydell, David K.
Abstract: New δ 13 Ccarb data from the most stratigraphically extensive graptolitic sections of Homerian age in the study area are reported from Wenlock Edge and the Ludlow Anticline (UK). These sections, situated upon the Midland Platform (Avalonia), were key in establishing the Homerian graptolite biozonation used within the type Wenlock Series, and are consequently of international importance. Based upon 162 δ 13 Ccarb samples from four outcrops (Eaton Track, Longville–Stanway Road Cutting, Burrington Section and Mortimer Forest Stop 1), new graptolite collections and a re-evaluation of the original graptolite collections, the onset of both lower (older) and upper (younger) peaks of the Homerian Carbon Isotope Excursion have been calibrated to a revised graptolite biozonation ( lundgreni – nassa – praedeubeli - deubeli – ludensis biozones). In addition, high-resolution correlation between the Ludlow Anticline and Wenlock Edge has been achieved by bio-, chemo- and sequence stratigraphic techniques. These correlations suggest a uniformity of depositional rates across the study area and indicate minor diachroneity at the base of the Much Wenlock Limestone Formation. Finally, correlations of the Midland Platform Homerian Carbon Isotope Excursion have allowed for better comparisons with other sections from which high-resolution graptolite and carbon isotope data are available. Such comparisons highlight the pan-regional synchronicity of the Homerian Carbon Isotope Excursion .